The Pacification of Favelas of Rio de Janeiro: A Neoliberal Twist to an Old-Fashioned Intervention - Pier Angelli, De Luca Maciel (Université d'Ottawa / University of Ottawa, 2015)
In 2008, a policy to address the territorialisation of the drug trade in Rio de Janeiro’s favelas was developed: the pacification of favelas. It involves two key elements, policing and local development, which are said to work in tandem to conquer the territory from drug dealers and integrate these areas to the city. Drawing from the literature on the governance of marginalized areas and neoliberal practices of security, this study explores how the pacification of favelas unfolds within a neoliberal context. The findings of this study are based on a thematic analysis of twenty-five in-depth interviews with key actors involved in the development and implementation of three core projects of the policy (the Pacifying Police Unit and two projects that coordinates social efforts, UPP Social and Peace Territories). Using the theoretical lenses of pacification proposed by Neocleous (2011) and Rigakos (2011), this research argues that the pacification of favelas can be considered a "project of pacification" (Rigakos, 2011). The analysis demonstrates that the dual strategy of the policy reinforces neoliberal practices to govern through fear, resulting in the militarization of favelas. Moreover, this study also finds that this policy serves capitalist interests when implemented within a neoliberal framework, even though its core elements resemble interventionist initiatives of colonial enterprises. My findings also reveal that some participants resist the implementation of initiatives based on a neoliberal framework. However, although their actions seek to emancipate and build an ethical community in favelas, based on long-term and fraternal bonds, the mainstream approach is still prevalent. As a result, favelas are progressively turned into aesthetic communities in which the interests of the market are the driving force.
Keywords: Pacification; Security; Neoliberalism; Marginalized areas; Urban Renewal; Militarization; Favelas; Police power